Purtscher-like retinopathy and paracentral acute middle maculopathy associated with improper antihypertensive drug use: a case report - Meng, Yang; Sawut, Abdulla; Tian, Miao; Li, Ying; Cai, Liwei; Xiao, Di; Yi, Zuohuizi; Chen, Changzheng (Frontiers in Medicine, 2024)
Background: Purtscher-like retinopathy (PLR) is a rare retinal microangiopathy with unclear pathogenesis. Paracentral acute middle maculopathy (PAMM) is an optical coherence tomography (OCT) sign proposed in recent years, which is characterized by infarction of the middle layer of the retina. This article reported a rare case of PRL and PAMM probably related to improper antihypertensive drug use in a middle-aged male.Case Presentation: A 49-year-old man presented with a complaint of sudden-onset vision loss and paracentral scotomas in the right eye for approximately one week. At presentation, the best-corrected visual acuity (BCVA) was 20/63 OD and 20/20 OS. Fundus examination showed multiple cotton-wool spots and Purtscher flecken in the posterior segment of the right eye. OCT revealed hyper-reflectivities in the inner nuclear layer (INL), consistent with PAMM. En face OCT showed PAMM's characteristic "fern-like" perivenular changes. Fluorescein angiography demonstrated prolonged arm-to-retina time, delayed artery and venous filling, and hypofluorescence corresponding to cotton-wool spots. Examinations of the left eye were unremarkable. Many imaging and laboratory tests were performed to detect the possible cause of PLR and PAMM, but no possible explanation was found except improper antihypertensive drug use. The patient was recommended to stop his antihypertensive medication, and prescribed other systemic medicines, including oral prednisolone (40 mg q.d. with gradual tapering), oral cobalamin (0.5 mg t.i.d.), and subcutaneous injections of compound anisodine (2.0 ml q.d.) beside the superficial temporal artery. Two weeks after onset, his BCVA improved to 20/25 in the right eye. During follow-ups, his BCVA recovered to 20/20, accompanied by the regression of fundus lesions. The patient reported no treatment-related adverse effects.Conclusions: This is the first reported case of PLR and PAMM following improper antihypertensive drug use. Our report expands our understanding of the etiology and pathophysiology of PLR and PAMM. We also stress the importance of proper application of medications in clinical practice.